The effects and mechanisms of SLC34A2 on maintaining stem cell-like phenotypes in CD147 breast cancer stem cells - Yonggang Lv; Ting Wang; Jing Fan; Zhenzhen Zhang; Juliang Zhang; Cheng Xu; Yongping Li; Ge Zhao; Chenyang He; Huimin Meng; Hua Yang; Zhen Wang; et al. (Tumor Biology)
The cancer stem cell (CSC) hypothesis has gained significant recognition in describing tumorigenesis. Identification of the factors critical to development of breast cancer stem cells (BCSCs) may provide insight into the improvement of effective therapies against breast cancer. In this study, we aim to investigate the biological function of SLC34A2 in affecting the stem cell-like phenotypes in BCSCs and its underlying mechanisms. We demonstrated that CD147 + cells from breast cancer tissue samples and cell lines possessed BCSC-like features, including the ability of self-renewal in vitro, differentiation, and tumorigenic potential in vivo. Flow cytometry analysis showed the presence of a variable fraction of CD147 + cells in 9 of 10 tumor samples. Significantly, SLC34A2 expression in CD147 + BCSCs was enhanced compared with that in differentiated adherent progeny of CD147 + BCSCs and adherently cultured cell line cells. In breast cancer patient cohorts, SLC34A2 expression was found increased in 9 of 10 tumor samples. By using lentiviral-based approach, si-SLC34A2-transduced CD147 + BCSCs showed decreased ability of sphere formation, cell viability in vitro, and tumorigenicity in vivo, which suggested the essential role of SLC34A2 in CD147 + BCSCs. Furthermore, PI3K/AKT pathway and SOX2 were found necessary to maintain the stemness of CD147 + BCSCs by using LY294002 or lentiviral-si-SOX2. Finally, we indicated that SLC34A2 could regulate SOX2 to maintain the stem cell–like features in CD147 + BCSCs through PI3K/AKT pathway. Therefore, our report identifies a novel role of SLC34A2 in BCSCs’ state regulation and establishes a rationale for targeting the SLC34A2/PI3K/AKT/SOX2 signaling pathway for breast cancer therapy.